Identification of two novel variants of the BCL11B gene in two Chinese pedigrees associated with neurodevelopmental disorders - Che, Fengyu; Tie, Xiaoling; Lei, Hong; Zhang, Xi; Duan, Mingyue; Zhang, Liyu; Yang, Ying (Frontiers in Molecular Neuroscience, 2022)
Objective According to a recent report, the mutation of transcription factor gene BCL11B is associated with the development of neurodevelopmental disorders and immune deficiency. By analyzing both clinical features and genetic variations, this study aims to reveal the genetic etiology of four patients with neurodevelopmental disorders from two unrelated Chinese pedigrees. Methods From the 4 cases, the clinical data were collected. The potential pathogenic gene variations were analyzed by means of based-trio whole exome sequencing (Trio-WES) and then validated through Sanger sequencing in their respective pedigrees. Furthermore, both the in vitro minigene assay and the NMD assay were performed to evaluate the impact of splicing and frameshift variants. Results The 4 patients displayed mild-to-severe intellectual developmental disorder, which was accompanied by speech delay, dysmorphic facies, and serious caries. In addition, the extended phenotype of developmental regression was observed in the proband from Family 1, which has been unreported previously. Molecular analysis was conducted to identify two novel heterozygous variants in the BCL11B gene: a maternal splicing variant c.427 + 1G > A in Family 1 and a de novo frameshift variant c.2461_2462insGAGCCACACCGGCG (p.Glu821Glyfs*28) in Family 2. As revealed by the in vitro minigene assay, the c.427 + 1G > A variant activated a new cryptic splice site. As confirmed by an overexpression assay, there was no significant difference in the level of mRNA and protein expression between the mutate-BCL11B (p.Glu821Glyfs*28) and the wild type. It confirms that p.Glu821Glyfs*28 variant could be an NMD escaping variant. Conclusion The extended phenotype of BCL11B-related disorders is reported in this study to reveal the clinical and genetic heterogeneity of the disease. The study starts by identifying a splicing variant and a novel frameshift variant of the BCL11B gene, thus confirming its aberrant translation. The findings of this study expand the mutation spectrum of the genetic BCL11B gene, which not only improves the understanding of the associated neurodevelopmental disorders from a clinical perspective but also provides guidance on diagnosis and genetic counseling for patients.